Tradisi Menghafal dalam Islam: Akar Peradaban, Relevansi Kontemporer, dan Solusi Pendidikan bagi Kecanduan Gim serta Degradasi Moral - Iman Hendra Yani; Maimun; Mira Mareta (Mataram University, 2026)
The rapid expansion of digital technology has contributed to growing concerns about gaming addiction and moral degradation among Muslim youth. Data from the World Health Organization (WHO) indicate that gaming disorder affects approximately 3-4% of gamers globally, while a 2023 survey by the Indonesian Child Protection Commission (KPAI) found that 62% of Indonesian adolescents reported spending more than four hours per day on digital games. This article aims to examine the relevance of the Islamic memorization tradition as a response to these contemporary challenges. Using a qualitative library research approach, the study analyzes the Quran, Hadith, classical Islamic literature, and recent studies in Islamic education, cognitive psychology, neuroscience, and digital media. Data were analyzed through content analysis to explore the relationship between memorization practices, cognitive development, and character formation. The findings reveal that memorization in Islam is not merely a cognitive activity but an educational tradition that integrates intellectual, moral, and spiritual development. This study further identifies that the cognitive values embedded in Islamic memorization practices such as the cultivation of attention, self-discipline, and emotional regulation align with executive function capacities documented in neuroscience, and may serve as a counter-framework to the behavioral and moral effects of excessive digital gaming. The study concludes that revitalizing the Islamic memorization tradition can serve as a relevant educational strategy for strengthening character and addressing the cognitive and moral challenges of the digital era.